Thermoresponsive electrospun fibres for anticancer drug delivery - Fatimah Fatimah; Gareth R. Williams (Next Materials)
We report a series of temperature-responsive nanofibre drug delivery systems prepared by electrospinning thermoresponsive poly(oligo(ethylene glycol) methyl ether methacrylate-co-di(ethylene glycol) methyl ether methacrylate) (p(OEGMA300-co-DiEGMA) with polycaprolactone (PCL). The nanofibres were loaded with ferulic acid (FA) as a model drug. After optimisation, smooth and cylindrical fibres were fabricated, with diameters up to 455 ± 214 nm. Infrared spectroscopy, X-ray diffraction and differential scanning calorimetry indicated that the FA was incorporated into the fibres as an amorphous solid dispersion. The wettability of the p(OEGMA300-co-DiEGMA)/PCL nanofibres changed with temperature, becoming more hydrophobic as the temperature rose. In vitro drug release studies demonstrated sustained release of FA, with different release profiles observed at 25 and 42 °C. The blank fibre materials exhibited good biocompatibility with Caco-2 cells, while those containing FA exhibited increased cytotoxic effects compared to pure FA. The fibres generated in this work could thus have applications such as developing implantable devices to treat cancer.